Shades of Sheol death and afterlife in the Old Testament - Johnston, Philip S. (Leicester, UK Apollos, 2002)
Inlcudes bibliographical references and indexes.
Keywords: Death -- religious aspects -- Christianity -- Old Testament teaching; Future life -- Christianity -- Old Testament teaching; Bible. O.T. -- criticism, interpretation, etc